2021
DOI: 10.3389/fimmu.2021.626776
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary Lymphoid Structure-B Cells Narrow Regulatory T Cells Impact in Lung Cancer Patients

Abstract: The presence of tertiary lymphoid structures (TLS) in the tumor microenvironment is associated with better clinical outcome in many cancers. In non-small cell lung cancer (NSCLC), we have previously showed that a high density of B cells within TLS (TLS-B cells) is positively correlated with tumor antigen-specific antibody responses and increased intratumor CD4+ T cell clonality. Here, we investigated the relationship between the presence of TLS-B cells and CD4+ T cell profile in NSCLC patients. The expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 46 publications
3
33
0
Order By: Relevance
“…The detection of LLT1 on GC B cells in these active mature TLS therefore supports a prognostic role of LLT1, consistent with the reported association with favorable outcome in NSCLC (54). TLS high tumors have been characterized by an increased proportion of activated effector/ memory CD8 + T cells and early differentiated, activated and nonregulatory CD4 + T cells (122,123). CD161 being expressed on effector/memory CD4 + and CD8 + T cells and being associated with better clinical outcome (54,79), these observations highlight the relevance of LLT1 and CD161 as biomarkers of active antitumor B cell and T cell immune responses.…”
Section: Llt1 and Cd161 As Biomarkers Of Ongoing Antitumor B Cell And...supporting
confidence: 84%
“…The detection of LLT1 on GC B cells in these active mature TLS therefore supports a prognostic role of LLT1, consistent with the reported association with favorable outcome in NSCLC (54). TLS high tumors have been characterized by an increased proportion of activated effector/ memory CD8 + T cells and early differentiated, activated and nonregulatory CD4 + T cells (122,123). CD161 being expressed on effector/memory CD4 + and CD8 + T cells and being associated with better clinical outcome (54,79), these observations highlight the relevance of LLT1 and CD161 as biomarkers of active antitumor B cell and T cell immune responses.…”
Section: Llt1 and Cd161 As Biomarkers Of Ongoing Antitumor B Cell And...supporting
confidence: 84%
“…Although dendritic cells are the major APCs that provide initial T cell activation in the lymph nodes, antigen-presenting B cells can contribute to additional CD4 + T cell expansion intratumorally, as demonstrated by ex vivo co-culture assays ( Bruno et al, 2017 ; Rossetti et al, 2018 ). Accordingly, in lung tumors, a high density of TLS B cells was associated with increased CD4 + T cell receptor repertoire clonality ( Zhu et al, 2015 ) and with a reduced percentage of Tregs ( Germain et al, 2021 ). The capacity of B cells to cross-present antigens to CD8 + T cells is also well established ( Heit et al, 2004 ; Hon et al, 2005 ; Marino et al, 2012 ) and has been demonstrated in the context of the cancer testis antigen NY-ESO-1 ( Gnjatic et al, 2003 ).…”
Section: Anti-tumor Role Of Tls B Cellsmentioning
confidence: 99%
“…And tumor-infiltrating follicular regulatory T cells, which are primarily located within TLSs and exhibit superior suppressive capacity and in vivo persistence as compared with Treg cells, could impair the survival of patients and impede the efficacy of immunotherapy treatment by regulating TLS ( 32 ). Nevertheless, a retrospective study showed that high TLS-B cell density could counterbalance the deleterious impact of high Treg cell density on survival of untreated NSCLC patients ( 33 ). It is difficult to fully assess TLSs and Treg cells by biopsy before neoadjuvant immunotherapy, while Treg cells in the posttreatment tumor tissue of this patient were deemed to impair anti-tumor immune response.…”
Section: Discussionmentioning
confidence: 99%